2010
DOI: 10.1016/j.ccr.2010.10.025
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant Human Erythropoietin Antagonizes Trastuzumab Treatment of Breast Cancer Cells via Jak2-Mediated Src Activation and PTEN Inactivation

Abstract: SUMMARY We found that the receptor for erythropoietin (EpoR) is coexpressed with human epidermal growth factor receptor-2 (HER2) in a significant percentage of human breast tumor specimens and breast cancer cell lines. Exposure of HER2 and EpoR dual-positive breast cancer cells to recombinant human erythropoietin (rHuEPO) activated cell signaling. Concurrent treatment of the cells with rHuEPO and trastuzumab reduced the cells’ response to trastuzumab both in vitro and in vivo. We identified Jak2-mediated activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
131
2
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 126 publications
(141 citation statements)
references
References 35 publications
7
131
2
1
Order By: Relevance
“…S6A). This result is consistent with findings from recent studies reporting that Jak2 directly phosphorylates Src and impacts the behavior of cancer cells (49,50). Importantly, we further demonstrated that the AhR protein adaptor is essential for Jak2-Src interaction in NSCLC.…”
Section: Discussionsupporting
confidence: 82%
“…S6A). This result is consistent with findings from recent studies reporting that Jak2 directly phosphorylates Src and impacts the behavior of cancer cells (49,50). Importantly, we further demonstrated that the AhR protein adaptor is essential for Jak2-Src interaction in NSCLC.…”
Section: Discussionsupporting
confidence: 82%
“…25,26 As shown in Fig. 2A, overexpression of HER2 does not lead to a decrease but rather a moderate increase in the MFI value of HLA-ABC expression in MCF7-HER18 cells compared to MCF7 cells.…”
Section: Resultsmentioning
confidence: 96%
“…Src inhibition appears to be important to trastuzumab-mediated anti-cancer activity, as increased Src signaling is associated with trastuzumab resistance (Mitra, 2009;Liang, 2010;. One mechanism leading to increased Src activity appears to be a variant of HER2 called HER2 delta 16 (Mitra, 2009), which shows increased oncogenic activity.…”
Section: Targeting Src In Her2-overexpressing Breast Cancermentioning
confidence: 99%
“…Dual targeting of HER2Delta16 plus Src with dasatinib resulted in Src inactivation, destabilization of HER2Delta16, and decreased tumorigenicity (Mitra, 2009). In addition, Src activation via Jak2 has been shown to reduce trastuzumab activity (Liang, 2010). Recombinant human erythropoietin activated Jak2-Src signaling and inactivated PTEN in HER2-positive cells (Liang, 2010).…”
Section: Targeting Src In Her2-overexpressing Breast Cancermentioning
confidence: 99%